GROWTH AND DEVELOPMENT OF PUMPKIN PLANTS OF THE USUAL UKRAINIAN VARIETY (MULTI-FRUIT) DEPENDING ON THE TIMES OF SOWING IN THE CONDITIONS OF THE RIGHT BANK FOREST STEPPE OF UKRAINE - Овчарук, Василь; Овчарук, Олег; Євстафієва, Юлія (SWorldJournal, 2024)
One of the main technological measures of cultivation, aimed at increasing the yield of ordinary multi-fruited pumpkin as a fodder crop, an important role belongs to the timing of sowing according to the level of the temperature regime of the soil for dee